The Frequency Of Empyema/Gangrene In Acute Cholecystitis And Its Relationship With Gender - Saniya Ahmed, Rabia Bint-e- Iftikhar, Mehreen Fatima, Saniya Ahmed, Rabia Bint-e- Iftikhar, Mehreen Fatima (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Cholecystectomy is one of the most frequently performed surgical procedures across the globe and is considered as a treatment of choice for majority cases of acute cholecystitis. Empyema/gangrene is one of the most frequent and important complication of acute cholecystitis. World over, the association between gender and the complications associated with acute cholecystitis is poorly documented. The purpose of the study was to find out the frequency of empyema/gangrene in acute cholecystitis and to determine its relation with gender. Methods: This cross-sectional descriptive study, was conducted at histopathology laboratory, Department of Pathology, Holy Family Hospital, Rawalpindi, by reviewing past medical record of (2016) of 76 patients(38 males and 38 females) of acute cholecystitis selected on the basis of nonprobability consecutive sampling. Data was analysed using SPSS 23. Results: Out of 76 patients, 25(32.9%) patients of acute cholecystitis developed empyema/gangrene. Out of 38 males, 17(45%) developed empyema/gangrene as a complication whereas out of 38 females only 8(21%) developed empyema/gangrene. A statistically significant portion of male patients developed empyema/gangrene, [p=0.028]. Conclusion: Male gender has a statistically significant relationship of developing empyema/gangrene in acute cholecystitis. This may help in prioritizing the patients for surgery. Keywords: Bladder, Male gender.